Intermolecular alkene and alkyne hydroacylation with beta-S-substituted aldehydes: mechanistic insight into the role of a hemilabile P-O-P ligand. - Moxham, G; Randell-Sly, H; Brayshaw, S; Weller, A; Willis, M (2008)
A straightforward to assemble catalytic system for the intermolecular hydroacylation reaction of beta-S-substituted aldehydes with activated and unactivated alkenes and alkynes is reported. These catalysts promote the hydroacylation reaction between beta-S-substituted aldehydes and challenging substrates, such as internal alkynes and 1-octene. The catalysts are based upon [Rh(cod)(DPEphos)][ClO(4)] (DPEphos=bis(2-diphenylphosphinophenyl)ether, cod=cyclooctadiene) and were designed to make use of the hemilabile capabilities of the DPEphos ligand to stabilise key acyl-hydrido intermediates against reductive decarbonylation, which results in catalyst death. Studies on the stoichiometric addition of aldehyde (either ortho-HCOCH(2)CH(2)SMe or ortho-HCOC(6)H(4)SMe) and methylacrylate to precursor acetone complexes [Rh(acetone)(2)(DPEphos)][X] [X=closo-CB(11)H(6)Cl(6) or [BAr(F) (4)] (Ar(F)=3,5-(CF(3))(2)C(6)H(3))] reveal the role of the hemilabile DPEphos ligand. The crystal structure of [Rh(acetone)(2)(DPEphos)][X] shows a cis-coordinated diphosphine ligand with the oxygen atom of the DPEphos distal from the rhodium. Addition of aldehyde forms the acyl hydride complexes [Rh(DPEphos)(COCH(2)CH(2)SMe)H][X] or [Rh(DPEphos)(COC(6)H(4)SMe)H][X], which have a trans-spanning DPEphos ligand and a coordinated ether group. Compared to analogous complexes prepared with dppe (dppe=1,2-bis(diphenylphosphino)ethane), these DPEphos complexes show significantly increased resistance towards reductive decarbonylation. The crystal structure of the reductive decarbonylation product [Rh(CO)(DPEphos)(EtSMe)][closo-CB(11)H(6)I(6)] is reported. Addition of alkene (methylacrylate) to the acyl-hydrido complexes forms the final complexes [Rh(DPEphos)(eta(1)-MeSC(2)H(4)-eta(1)-COC(2)H(4)CO(2)Me)][X] and [Rh(DPEphos)(eta(1)-MeSC(6)H(4)-eta(1)-COC(2)H(4)CO(2)Me)][X], which have been identified spectroscopically and by ESIMS/MS. Intermediate species in this transformation have been observed and tentatively characterised as the alkyl-acyl complexes [Rh(CH(2)CH(2)CO(2)Me)(COC(2)H(4)SMe)(DPEphos)][X] and [Rh(CH(2)CH(2)CO(2)Me)(COC(6)H(4)SMe)(DPEphos)][X]. In these complexes, the DPEphos ligand is now cis chelating. A model for the (unobserved) transient alkene complex that would result from addition of alkene to the acyl-hydrido complexes comes from formation of the MeCN adducts [Rh(DPEphos)(MeSC(2)H(4)CO)H(MeCN)][X] and [Rh(DPEphos)(MeSC(6)H(4)CO)H(MeCN)][X]. Changing the ligand from DPEphos to one with a CH(2) linkage, [Ph(2)P(C(6)H(4))](2)CH(2), gave only decomposition on addition of aldehyde to the acetone precursor, which demonstrated the importance of the hemiabile ether group in DPEphos. With [Ph(2)P(C(6)H(4))](2)S, the sulfur atom has the opposite effect and binds too strongly to the metal centre to allow access to productive acetone intermediates.